Health issues of large dams: the case of Soum in the West Central Region of Burkina Faso - Korotimi, Sanou; Isidore, Yanogo Pawendkisgou; Joseph, Yaméogo; Richard, Zongo (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study analyses the sanitary stakes of the watering of the Soum dam. To do so, a review of the literature on the subject of research, surveys of 165 farmers, interviews with three health agents and direct observations were carried out. The study shows that the Soum dam contributes to the improvement of farmers' health conditions. Indeed, their attendance at the HSPC (Health and Social Promotion Center) increased from 36.13% before the construction of the dam to 62% after its effective operation. As a result, the use of traditional medicine decreased by 12.9% after the installation of the dam. In addition, the classes of money invested in the purchase of medicines increased. There were three classes of annual amounts ranging from 5,000 FCFA/household to 75,000 FCFA/household before the installation of the dam. After the installation of the dam, there are four, with amounts ranging from 5,000 FCFA/household/year to 100,000 FCFA/household/year. However, the dam creates a humid environment favourable to the proliferation of mosquitoes, particularly female anopheles. As a result, 95.48% of the respondents are exposed to malaria. Also, socio-economic activities such as market gardening and the consumption of untreated water from the dam present health risks that the authorities in charge of the management of the dam must take into account by raising awareness and providing continuous support through the distribution of mosquito nets. This study also showed that the health aspect is important and must be taken into account in the same way as the economic and food aspects.